Consequences of Delaying Management of Inguinal Hernia: A Case Report of Enterocutaneous Fistula in a Child - Obadiah, Dr Abraham Agaya; Umar, Dr Aminu Muhammed; Chukwurah, Dr Uchechukwu Alex; Olori, Dr Samson (International Journal of Innovative Research in Medical Science, 2025)
Introduction: Inguinal hernia is one of the most common surgical conditions worldwide. However, in some resource-limited regions, delays in surgical repair still remain an issue. These delays are often driven by systemic barriers such as high patient loads, limited healthcare access, and cultural beliefs about health. One rare but severe complication of delayed treatment is enteroscrotal fistula. Case Presentation: An 18-month-old boy presented with a 3-week history of a progressively enlarging left scrotal swelling, accompanied by a 3-day history of fecal discharge from the scrotum. The swelling became acutely painful shortly before admission. His caregivers had delayed seeking care, believing the condition would resolve spontaneously. Examination findings suggested an enteroscrotal fistula secondary to a strangulated inguinal hernia. Following initial resuscitation, surgical exploration found an ileal perforation. Resection and end-to-end anastomosis, herniotomy, and scrotal wound debridement were done. Recovery was uneventful, and the patient was discharged on postoperative day 7 in good condition. Discussion: This case highlights the potentially life-threatening consequences of delayed hernia management in resource-limited regions. While inguinal hernias are typically managed electively, systemic delays increase the risk of serious complications. Enteroscrotal fistula is extremely rare and carries a significant risk of infection, tissue loss, and even mortality if not promptly treated. This case shows the urgent need for improved caregiver education and broader access to timely surgical care. Strengthening primary healthcare systems and referral networks is essential in preventing avoidable morbidity in similar contexts.